Advanced Modelling and Performance Analysis of a Separately Excited Direct-Current Motor Powered by Photovoltaic Generators Using Maximum Power Point Tracking Techniques - Feras Alasali; Tha’er O. Sweidan; Mohammed I. Abuashour; William Holderbaum (Journal of Low Power Electronics and Applications)
The integration of photovoltaic (PV) systems into DC motor drives has prompted the enhancement of motor performance. This study explores the application of photovoltaic generators (PVs) to independently power and excite a Separately Excited Direct-Current (SEDC) system by utilizing a proportional open-circuit voltage method as a strategy for tracking the maximum power point. This approach offers an effective means of optimizing energy output from PV systems. The primary aim was to optimize power output from photovoltaic generators across varying solar intensity levels. This paper describes the nonlinear current/voltage behaviour of PV generators under different levels of irradiation, along with the magnetic characteristics of the core material in an SEDC motor, utilizing advanced polynomial equations for accurate mathematical representation. Furthermore, we conducted a dynamic analysis of the SEDC motor, powered by the PV generators, under varying solar intensities. This study investigates the operational performance of the SEDC motor under varying solar irradiance levels by developing a realistic model using MATLAB software, R2022a, for numerical simulations, followed by implementation on high-performance computing platforms, including a real-time simulator and testbed, using a real-time digital simulator (RTDS).